How Large are Global Energy Subsidies? - David Coady; Ian Parry; Louis Sears; Baoping Shang (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper estimates fossil fuel subsidies and the economic and environmental benefits from reforming them, focusing mostly on a broad notion of subsidies arising when consumer prices are below supply costs plus environmental costs and general consumption taxes. Subsidies are 4.9 trillion worldwide in 2013 and 5.3 trillion in 2015 (6.5 percent of global GDP in both years). Undercharging for global warming accounts for 22 percent of the subsidy in 2013, air pollution 46 percent, broader vehicle externalities 13 percent, supply costs 11 percent, and general consumer taxes 8 percent. China was the biggest subsidizer in 2013 (1.8 trillion), followed by the United States (0.6 trillion), and Russia, the European Union, and India (each with about 0.3 trillion). Eliminating subsidies would have reduced carbon emissions in 2013 by 21 percent and fossil fuel air pollution deaths 55 percent, while raising revenue of 4 percent, and social welfare by 2.2 percent, of global GDP.
Keywords: Q31; Q38; Q48; 330; energy subsidies; global warming; air pollution; efficient taxation; deadweight loss; revenue